Categorizing Data Quality Issues To Risk Level on Medicine and Food Inspector - fitria, Fitria; Sitorus, Michael (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2019)
Nowadays, data quality is important for every organization who need high quality of information for their business process. In the data flow of organization, every second has possibilities to occur data quality issues. Organization has to assess what the causes, impact of issues, and how to mitigate. In this paper, will describe and guide the organization to classify data quality issues to risk level. Its to make priority mitigate easier for management decision making especially on medicine and food inspector